ASSESSMENT OF KNOWLEDGE REGARDING EVIDENCE BASED GUIDELINES ON VAP PREVENTION AMONG NURSES - KOUSER , N; KHAN, N; AMIR , Z; TASNEEM SS, SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Ventilator-associated pneumonia (VAP) is a serious healthcare-associated infection that increases morbidity, mortality, and healthcare costs, particularly in intensive care units (ICUs). In Pakistan, the high prevalence of VAP in ICUs underscores the importance of adherence to evidence-based preventive practices among nursing staff. However, knowledge gaps and inconsistencies in VAP preventive practices remain a challenge, largely due to limited training resources and high patient-to-nurse ratios. Objective: This study aimed to assess the knowledge of ICU nurses on evidence-based guidelines for VAP prevention at a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study design was utilized. Data were collected from 140 registered nurses working in the ICU of Sir Ganga Ram Hospital, Lahore, using a structured questionnaire consisting of 17 questions related to VAP prevention guidelines. Convenience sampling was employed to recruit participants who met the inclusion criteria. Data analysis was performed using SPSS, with descriptive statistics applied to summarize findings and identify knowledge gaps. Results: The study revealed varied levels of knowledge among ICU nurses regarding VAP prevention. While the majority demonstrated awareness of core practices, such as semi-recumbent positioning and regular oral care, there were notable gaps in understanding related to the frequency of ventilator circuit changes and the optimal use of suction systems. Approximately 67.9% of nurses were aware of general VAP guidelines, but only 47.1% correctly identified all recommended practices. Additionally, knowledge disparities were observed based on educational background and years of ICU experience. Conclusion: This study highlights critical knowledge gaps among ICU nurses regarding evidence-based VAP prevention practices. The findings underscore the need for targeted educational interventions and standardized training programs to improve adherence to VAP guidelines. Strengthening nurse education on VAP prevention can contribute to reduced infection rates, enhanced patient safety, and better utilization of healthcare resources in Pakistan’s ICUs.